THE EFFECTIVENESS OF MOVIE MAKING ACTIVITIES TO IMPROVE STUDENTS’ LEARNING MOTIVATION AND SPEAKING SKILL (An Experiment Research Third Semester of Port and Shipping Management Students Of STIMART “AMNI” Semarang in the Academic Year of 2016/2017) - Ariana Oktavia (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2018)
The purpose of this study was to find out on the effectiveness of movie making activities to improve students’ learning motivation and speaking skills of the third semester of Port and Shipping management students of STIMART “AMNI” Semarang in the academic year of 2016/2017. This research was an experimental research design which involved two groups. They were control group and experimental group. The subject of this research was Class A and B of the third semester of Port and Shipping Management of STIMART “AMNI” Semarang in the academic year of 2016/2017. Each class was consists of 30 students. Class A was experiment group and class B was the control group. At the beginning of this research, both groups were given pretest. Then, the experimental group was given treatment of movie making activities which was done for five times. The control group was not getting any treatment. Next, both groups were given posttest.The result of this research was based on the result of both groups pretest and posttest. The control group pretest result was 60, 6 and the posttest result was 77,2 while the experimental group pretest result was 67,4 and the posttest result was 83,4 so, it could be concluded that movie making activities was 83,4% effective to improve and increase students’ learning motivation and speaking skills of Port and Shipping management students of STIMART “AMNI ” Semarang in the academic year of 2016/2017.Keywords : Movie making activities, Speaking, Motivation. Tujuan dari penelitian ini adalah untuk mengetahui keefektifan kegiatan pembuatan film untuk meningkatkan motivasi belajar siswa dan ketrampilan berbicara taruna semester tiga jurusan Ketatalaksanaan pelayaran Niaga dan Kepelabuhanan STIMART “ AMNI ” Semarang tahun akademik 2016/2017.  Penelitian ini adalah penelitian experimental yang melibatkan 2 grup. 1 grup sebagai control grup dan 1 grup sebagai experimental grup. Subjek dari penelitian ini adalah taruna kelas A dan B mempunyai jumlah taruna sebanyak 30 taruna . Kelas A sebagai eksperiment grup dan kelas B sebagai kontrol grup. Pada awal pelaksanaan penelitian , kedua grup diberikan pretest . Kemudian , kelas yang merupakan eksperimental grup diberikan perlakuan menggunakan kegiatan pembuatan film. Perlakuan ini dilakukan lima kali . Bagi control grup tidak diberikan perlakuan sama sekali. Selanjutnya, kedua grup diberikan posttest. Hasil dari penelitian ini berdasarkan hasil dari pretest dan posttest dari kedua grup. Hasil pretest dari control grup 60,6 dan posttestnya 77,2 sedangkan hasil pretest eksperimental group 67,4 dan posttestnya 83,4 jadi dapat disimpulkan bahwa kegiatan pembuatan film 83,4% efektif untuk meningkatkan motivasi belajar siswa dan ketrampilan berbicara taruna semester tiga jurusan Ketatalaksanaan Pelayaran Niaga dan Kepelabuhanan STIMART “ AMNI ”Semarang tahun akademik 2016/2017.Kata kunci : Kegiatan pembuatan Film, Berbicara, Motivasi